Key material for preparing flame-retardant and light-resistant core-shell type water-based acrylate resin coating
By introducing specific flame retardant and light-resistant modifiers into the core and shell layers of the acrylate resin, the problems of melt droplet generation, poor flame retardancy and insufficient light resistance during ignition are solved, and higher flame retardancy and light resistance are achieved.
Patent Information
- Application Number
- CN202411774244.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2025-03-11
AI Technical Summary
Acrylate resin coatings will produce melt droplets when they catch fire, causing the fire to expand, and their flame retardancy and light resistance are poor, limiting their application range.
Carbon-forming 9,10-dihydro-9-oxa-10-phosphophenophen-10-oxide (DOPO) and organic molybdenum compounds with good smoke inhibition were introduced into the core layer of the acrylate resin, and hydroxypropylprogyl ether with bright reflection and light-absorbing coumarin derivatives were introduced into the shell layer, and these substances were introduced into the acrylate ester resin segments through copolymerization reaction.
The triple effect of flame retardant and smoke suppression of acrylate resins is achieved, and its light resistance and reflectivity are significantly improved.
Smart Images

Figure BDA0005171015430000111 
Figure BDA0005171015430000121 
Figure BDA0005171015430000131
Abstract
Description
[0001] The present invention is a divisional of No. 2024112881583. Technical Field
[0002] The invention relates to a method for preparing a water-based acrylic resin coating, in particular to a method for preparing a flame-retardant and light-resistant core-shell water-based acrylic resin coating. Background Art
[0003] Polyacrylate is a type of polymer synthesized from acrylic acid or methacrylate as the main raw material. It has good mechanical properties, weather resistance and acid and alkali resistance. Its preparation process is simple and the cost is low. It is widely used as a film-forming material for leather finishing, architectural coatings and wood. However, due to the poor flame retardancy and light resistance of pure polyacrylate, its application range is limited. Therefore, its performance can be improved through chemical modification and structural design.
[0004] Zhang Chi et al. prepared an intumescent water-based fire retardant coating using ammonium polyphosphate as an acid source, pentaerythritol as a carbon source, dicyandiamide and diammonium hydrogen phosphate as gas sources, and thermosetting water-based epoxy emulsion and synthetic acrylic ester emulsion as film-forming materials. The fire resistance was studied by simulating large-plate combustion, and the composition of the expanded carbon layer after burning was analyzed by Fourier transform infrared spectrometer (FTIR), and the carbon pores of the carbon layer were observed by electron microscopy. The results show that thermosetting water-based epoxy emulsion can effectively improve the fireproof and heat-insulating properties of intumescent vinegar-acrylic fire retardant coatings. When the addition amount is 9wt%, the overall strength of the carbon layer reaches 3.22N / cm after burning for 60 minutes. 2 The expansion ratio is 36 times, and the back-fire temperature of the wood board is only 61°C. The flame retardant is mixed with the acrylic emulsion by a compounding method. The method is simple, but the flame retardancy is poor by immersion absorption of the compound, and the light resistance of the acrylic resin is not involved.
[0005] The invention patent CN112409877A uses water, emulsifier, methacrylic acid and acrylic acid, heats to 45°C, stirs for 40 minutes, adds A monomer, and the emulsification time is 30 to 70 minutes; heats to 65°C and starts to reflux water, heats to 77°C and keeps warm, drips 0.3 to 0.7 parts by weight of initiator A, and the dripping time lasts for 1 to 3 hours, reacts for 2 to 4 hours, and obtains a core layer emulsion; simultaneously drips B monomer and 0.3 to 0.4 parts by weight of initiator A into the obtained core layer emulsion, and the dripping time lasts for 1 to 2 hours , keep warm at 75-85°C and stir to react for 3 hours, then add 0.6-1.1 weight parts of flame retardant crosslinking agent, keep warm at 75-95°C for 1-3 hours, cool to 50°C, add 0.3 weight parts of emulsifier, react for 30 minutes, add ammonia water to adjust the pH value to 7-8, and obtain the flame retardant water-based core-shell acrylic resin coating and paint. The obtained flame retardant water-based core-shell acrylic resin coating and paint have good flame retardancy, and the obtained acrylic resin does not involve the key points of smoke and droplet core.
[0006] Invention patent CN110204989A adopts urea to replace traditional formaldehyde, modifies dimethyl phosphite and acrylamide, and coordinates with stabilizing materials for the preparation of core-shell acrylic resins. The amount of droplets generated by the combustion of the prepared acrylic resin is further reduced, and both smoke and droplets are reduced, showing a great improvement, but it does not involve the light resistance of the acrylic resin.
[0007] Xu Weihuan and others sprayed plastic coatings on plastic surfaces and found that film-forming materials and titanium dioxide have a certain influence on the yellowing performance of plastic coatings. Coatings made from acrylic resins containing benzene rings have poor yellowing resistance and severe yellowing, while coatings made from 2310 titanium dioxide have good yellowing resistance and weaker yellowing. Ultraviolet absorbers can significantly improve the yellowing of plastic coatings. When the addition amount of ultraviolet absorbers is 0.3%, the yellowing resistance is the best and the yellowing color difference is the smallest. The ultraviolet absorber is combined with acrylic resins by physical mixing, but the ΔE exceeds 0.8, and the flame retardancy of acrylic resins is not involved, and the resulting acrylic acid is non-aqueous.
[0008] The invention patent CN108624183A synthesizes a self-made emulsifier, which changes the traditional acrylic resin synthesis that requires the addition of anionic and nonionic emulsifiers in the core-shell, p-aminobenzenesulfonamide as the catalyst of the emulsifier, tetramethylethylenediamine as the catalyst of the light-resistant material, and bromoacetyl to increase the light resistance, thereby improving the light resistance of acrylic resin. However, the invention does not involve improving the flame retardancy of acrylic resin, and only studies the light resistance of acrylic resin within 450 minutes.
[0009] In summary, when the film of acrylic resin coating catches fire, molten droplets will be produced, causing a larger fire. At the same time, acrylic resin has poor flame retardancy, and the color change under light affects the service life of acrylic resin. Therefore, it is very necessary to study it. Summary of the invention
[0010] The present invention introduces carbon-forming 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) and an organic molybdenum compound with good smoke suppression into the core layer of the acrylic resin, thereby achieving the triple effects of flame retardancy, droplet suppression and smoke suppression; at the same time, hydroxypropyl propargyl ether with bright reflection effect and light-absorbing coumarin derivatives are introduced into the shell layer, and the above substances are introduced into the acrylic resin chain segment by free radical reaction, so that the two act synergistically, the light resistance level and reflectivity of the acrylic monomer are improved, and thus the light resistance and flame retardancy of the acrylic resin are improved to a greater extent.
[0011] The method for preparing a flame-retardant and light-resistant core-shell water-based acrylic resin coating is characterized in that the coating is prepared according to the following steps:
[0012] (1) Preparing a core layer emulsion: adding 30-50 g of water, 1.2-1.9 g of emulsifier A, and 2.6-4.2 g of methacrylic acid to a reaction container, mixing and stirring evenly, heating to 40-45° C., stirring and reacting for 60 min, adding monomer A and 0.01 mol of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO), and 1.1-2.2 g of an organic molybdenum compound, and emulsifying for 20-30 min; heating to 65° C., passing reflux water, heating to 80-90° C., dripping 0.4-0.7 g of initiator, and continuing the dripping time for 1-1.5 h, and reacting at 70-90° C. for 1-2 h to obtain a core layer emulsion;
[0013] (2) adding all monomers B and 0.2-0.4 g of initiator to the core layer emulsion obtained in step (1) at the same time, the dropping time lasts for 1 hour, the reaction is stirred at 75-85° C. for 1.5 hours, 1.0-2.6 g of hydroxypropyl propargyl ether, 0.7-2.6 g of coumarin derivative and 0.02 g of glutaric acid are added, the reaction is carried out at 60-70° C. for 1 hour, the temperature is lowered to 50° C., 0.3 g of emulsifier B, 0.1 g of zirconium sulfate, 0.1-0.2 g of aluminum sulfate and 0.05 g of sodium maleate are added, the reaction time is 30 minutes, and ammonia water is added to adjust the pH value to 7-8 to obtain the flame-retardant and light-resistant core-shell water-based acrylic resin coating;
[0014] The monomer A is prepared by mixing 3-4g of ethyl acrylate, 4-5g of methyl methacrylate and 3-4g of hydroxyethyl acrylate;
[0015] The monomer B is prepared by mixing 2-6 g of ethyl acrylate, 4-8 g of methyl methacrylate and 3-6 g of hydroxyethyl acrylate.
[0016] The initiator is any one of ammonium persulfate, potassium persulfate and potassium hydrogen persulfate;
[0017] The preparation method of the organic molybdenum compound is:
[0018] (1) 0.1 mol of 1-bromotetradecane, 0.11-0.12 mol of N-methyldiethanolamine and 100 mL of acetonitrile reagent were added to a round-bottom flask in sequence, the temperature was slowly raised to 70-85° C., and the mixture was stirred at 200 rpm for 16-24 h. The acetonitrile solvent was removed by a vacuum evaporator, and 80-100 mL of ethyl acetate was added. After filtering, a white solid was obtained, which was washed with a small amount of ethyl acetate for 4-5 times, and vacuum dried at 60-75° C. for 32-48 h to obtain intermediate A;
[0019] (2) dissolving 0.11-0.12 mol of molybdenum acetylacetonate powder in hot ethanol, slowly adding 0.10-0.13 mol of alcohol solution of intermediate A while stirring, stirring evenly, heating to 70-85° C., reflux reaction for 16-24 hours, and removing the solvent by reduced pressure distillation to obtain a dark blue powder, namely intermediate B;
[0020] (3) 0.10 mol of intermediate B and 0.11 mol of oleic acid were dissolved in 60-70 mL of dichloromethane solution, and then 40 mL of 1-2 mol / L sodium hydroxide aqueous solution was added dropwise to the mixed solution. The mixture was stirred for 10-12 h, and the color of the product solution changed from dark blue to green. 30 mL of dichloromethane was taken to extract the product, and then the product was washed with distilled water until no precipitation was generated in the silver nitrate solution. The product was dried to obtain an organic molybdenum compound.
[0021] The preparation method of coumarin derivatives is as follows:
[0022] Add 2.62 g of glycine methyl ester hydrochloride and 15-20 mL of deionized water to a round-bottom flask, adjust the pH to 8.5-9.0 with triethylamine, add 5.51 g of salicylaldehyde to the reaction system, and react at room temperature for 12-24 h. During the reaction, an orange suspended substance appears in the bottle. Filter and wash to obtain an orange solid crude product, place it in a vacuum drying oven to dry, and use a DMF-H2O system for recrystallization to obtain 3-(2-(hydroxybenzylidene)amino)coumarin;
[0023] The prepared 3-(2-(hydroxybenzylidene)amino)coumarin was transferred into a 250mL three-necked flask, and 100mL of dilute hydrochloric acid (concentrated hydrochloric acid: water mixed in a volume ratio of 1:2) was added to the flask, and hydrolysis was carried out at room temperature for 30-60min, and the pH was adjusted to 8-9. A large amount of brown suspended matter was precipitated in the flask. After the flask was cooled, it was filtered and washed to obtain a reddish-brown solid, which was recrystallized using EtOH:H2O in a volume ratio of 1:3. Then 3-4g of acryloyl chloride and 10-20mL of toluene were added to the system, the pH was adjusted to 7.5, and the reaction was carried out at 40-50°C for 1-2h, and then dried to obtain a coumarin derivative.
[0024] Emulsifier A is prepared by mixing sodium dodecylbenzene sulfonate and AEO-9 in a mass ratio of 2:1.
[0025] Emulsifier B is AEO-9.
[0026] The positive effects of the present invention are:
[0027] (1) The present invention utilizes the copolymerization reaction of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) PH bond, the double bond in the acrylic ester monomer, and the double bond of the organic molybdenum compound under the action of an initiator, introduces carbon-forming 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) into the acrylic ester resin chain segment, and introduces an organic molybdenum compound with good smoke suppression. Due to the increase in rigidity and carbonization of DOPO, the combustion continuity decreases and the melt is difficult to drip, and it is difficult to produce molten droplets, thereby avoiding secondary hazards, reducing the combustible gas released by combustion, and improving flame retardancy. At the same time, the organic molybdenum compound can also suppress the release of smoke, thereby achieving the triple effects of flame retardancy, molten drop suppression, and smoke suppression.
[0028] (2) The present invention selects 1-bromotetradecane to react with N-methyldiethanolamine to form a quaternary ammonium salt compound with a hydroxyl group, and then uses molybdenum acetylacetonate to react with the quaternary ammonium salt compound to introduce the molybdenum compound into the system, and then introduces oleic acid with a double bond into the molybdenum compound under an alkaline environment, and copolymerizes the double bond in the molybdenum compound with an acrylate monomer, and introduces the acrylic resin chain segment introduced by the molybdenum compound to reduce the smoke generated by combustion;
[0029] (3) Using glycine methyl ester hydrochloride to react with salicylaldehyde to obtain 3-(2-(hydroxybenzylidene)amino) coumarin, and then using dilute hydrochloric acid to hydrolyze it to break the carbon-nitrogen double bond to form an amino group, so that the obtained coumarin derivative has an amino group, and reacts with the acyl chloride of acryloyl chloride to obtain a coumarin derivative with a double bond; introducing the coumarin derivative into the acrylic ester monomer chain segment to improve the light resistance of the acrylic ester monomer. The principle of coumarin derivatives to improve the light resistance of materials is that the two coumarin groups in the coumarin derivatives will undergo a [2+2] cycloaddition reaction under ultraviolet light near 365nm to generate a dimer with a cyclobutane structure. The optical activity of the coumarin functional group is relatively high. Under the conditions of ultraviolet light of different wavelengths, it can undergo reversible photodimerization and photodepolymerization near 254nm. It consumes energy through continuous polymerization and depolymerization, reducing the effect on the light resistance of acrylic resins, and no catalyst needs to be added during the entire reversible process;
[0030] (4) The present invention introduces hydroxypropyl propargyl ether with a bright reflective effect into the shell layer, and copolymerizes hydroxypropyl propargyl ether with acrylic ester monomers and introduces it into acrylic resin segments. The two cooperate with coumarin derivatives to improve the light resistance of acrylic ester monomers. Part of glutaric acid reacts with a small amount of hydroxyl groups of hydroxypropyl propargyl ether to introduce non-polar segments on hydroxypropyl propargyl ether, thereby increasing the surface smoothness of acrylic resin film. At the same time, zirconium sulfate and aluminum sulfate are introduced into the system. Aluminum sulfate and zirconium sulfate are hydrolyzed in water to become basic aluminum sulfate and basic zirconium sulfate. Basic aluminum sulfate or basic aluminum sulfate is complexed with the hydroxyl groups in the hydroxypropyl propargyl ether in the shell layer to effectively fix the hydroxypropyl propargyl ether, thereby improving the long-term light resistance of acrylic ester resin. Sodium maleate can inhibit the excessive hydrolysis of basic aluminum sulfate and basic zirconium sulfate and the violent reaction with hydroxypropyl propargyl ether. At the same time, zirconium sulfate can also improve the light resistance. DETAILED DESCRIPTION
[0031] Embodiment 1
[0032] The method for preparing a flame-retardant and light-resistant core-shell water-based acrylic resin coating is characterized in that the coating is prepared according to the following steps:
[0033] (1) Preparation of core layer emulsion: add 30g of water, 1.2g of emulsifier (sodium dodecylbenzene sulfonate and AEO-9 mixed in a weight ratio of 2:1), and 2.6g of methacrylic acid to a reaction container, mix and stir evenly, heat to 40°C, stir and react for 60min, add monomer A and 0.01mol of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO), and 1.1g of organic molybdenum compound, and emulsify for 20min; heat to 65°C, pass reflux water, heat to 80°C, drop 5.4g of ammonium persulfate solution dissolved in 5g of water, and continue to drop for 1h, and react at 70°C for 1h to obtain core layer emulsion;
[0034] (2) adding all the monomers B and 5.2 g of ammonium persulfate solution dissolved in 5 g of water to the core layer emulsion obtained in step (1) at the same time, the dropping time lasts for 1 hour, the reaction is stirred at 75° C. for 1.5 hours, and then 1.0 g of hydroxypropyl propargyl ether, 0.7 g of coumarin derivative and 0.02 g of glutaric acid are added, and the reaction is carried out at 60° C. for 1 hour, and the temperature is lowered to 50° C., and 0.3 g of emulsifier (emulsifier AEO-9), 0.1 g of zirconium sulfate, 0.1 g of aluminum sulfate and 0.05 g of sodium maleate are added, and the reaction time is 30 minutes. Ammonia water is added to adjust the pH value to 7-8 to obtain the flame-retardant and light-resistant core-shell water-based acrylic resin coating;
[0035] The monomer A is prepared by mixing 3g of ethyl acrylate, 4g of methyl methacrylate and 3g of hydroxyethyl acrylate;
[0036] The monomer B is prepared by mixing 2g of ethyl acrylate, 4g of methyl methacrylate and 3g of hydroxyethyl acrylate.
[0037] The preparation method of the organic molybdenum compound is:
[0038] (1) 0.1 mol of 1-bromotetradecane, 0.11 mol of N-methyldiethanolamine and 100 mL of acetonitrile reagent were added to a round-bottom flask in sequence, the temperature was slowly raised to 70° C., and the mixture was stirred at 200 rpm for 16 h. The acetonitrile solvent was removed by a vacuum evaporator, and 80 mL of ethyl acetate was added. A white solid was obtained after filtration, and the solid was washed with a small amount of ethyl acetate for 4 times and dried under vacuum at 60° C. for 32 h to obtain intermediate A;
[0039] (2) 0.11 mol of molybdenum acetylacetonate powder was dissolved in hot ethanol, and 0.10 mol of alcohol solution of intermediate A (30 mL of ethanol) was slowly added while stirring, and after stirring evenly, the mixture was heated to 70° C. and refluxed for 16 h. The solvent was removed by vacuum distillation to obtain a dark blue powder, namely intermediate B;
[0040] (3) 0.10 mol of intermediate B and 0.11 mol of oleic acid were dissolved in 60 mL of dichloromethane solution, and then 40 mL of 1 mol / L sodium hydroxide aqueous solution was added dropwise to the mixed solution. The mixture was stirred for 10 h, and the color of the product solution changed from dark blue to green. 30 mL of dichloromethane was taken to extract the product, and then the product was washed with distilled water until no precipitation was generated in a silver nitrate solution. The product was dried to obtain an organic molybdenum compound.
[0041] The preparation method of coumarin derivatives is as follows:
[0042] Add 2.62 g of glycine methyl ester hydrochloride and 15 mL of deionized water to a round-bottom flask, adjust the pH to 8.5-9.0 with triethylamine, add 5.51 g of salicylaldehyde to the reaction flask, and react at room temperature for 12 h. During the reaction, an orange suspended substance appears in the flask, and the orange solid crude product is filtered and washed to obtain the orange solid crude product, which is placed in a vacuum drying oven for drying and recrystallized using a DMF-H2O system to obtain 3-(2-(hydroxybenzylidene)amino)coumarin;
[0043] The prepared 3-(2-(hydroxybenzylidene)amino)coumarin was transferred into a 250mL three-necked flask, and 100mL of dilute hydrochloric acid (concentrated hydrochloric acid and water were mixed in a volume ratio of 1:2) was added to the flask for hydrolysis at room temperature for 30min, and the pH was adjusted to 8-9. A large amount of brown suspended matter was precipitated in the flask. After the flask was cooled, it was filtered and washed to obtain a reddish-brown solid, which was recrystallized using EtOH:H2O in a volume ratio of 1:3 and dried. Then 3g of acryloyl chloride and 10mL of toluene were added to the system, the pH was adjusted to 7.5, and the solution was reacted at 40°C for 1h and dried to obtain a coumarin derivative.
[0044] Embodiment 2
[0045] The method for preparing a flame-retardant and light-resistant core-shell water-based acrylic resin coating is characterized in that the coating is prepared according to the following steps:
[0046] (1) Preparing a core layer emulsion: adding 50 g of water, 1.9 g of an emulsifier prepared by mixing sodium dodecylbenzene sulfonate and AEO-9 in a mass ratio of 2:1, and 4.2 g of methacrylic acid to a reaction container, mixing and stirring evenly, heating to 45° C., stirring and reacting for 60 min, adding monomer A and 0.01 mol of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO), and 2.2 g of an organic molybdenum compound, and emulsifying for 30 min; heating to 65° C. and starting to reflux water, heating to 90° C., and dripping 5.7 g of a potassium persulfate initiator solution dissolved in 5 g of water, and continuing the dripping time for 1.5 h. The mixture was reacted at 90° C. for 2 h to obtain a core layer emulsion;
[0047] (2) To the entire core layer emulsion obtained in step (1), monomer B and 5.4 g of potassium persulfate initiator solution dissolved in 5 g of water were simultaneously added dropwise for 1 h, and the mixture was stirred at 85° C. for 1.5 h. 2.6 g of hydroxypropyl propargyl ether, 2.6 g of coumarin derivative and 0.02 g of glutaric acid were added, and the mixture was reacted at 70° C. for 1 h. The mixture was cooled to 50° C., 0.3 g of AEO-9, 0.1 g of zirconium sulfate, 0.2 g of aluminum sulfate and 0.05 g of sodium maleate were added, and the reaction time was 30 min. Ammonia water was added to adjust the pH value to 7-8, and the flame-retardant and light-resistant core-shell water-based acrylic resin coating was obtained.
[0048] Wherein, the monomer A is a mixture of 4g of ethyl acrylate, 5g of methyl methacrylate and 4g of hydroxyethyl acrylate;
[0049] The monomer B is prepared by mixing 6 g of ethyl acrylate, 8 g of methyl methacrylate and 6 g of hydroxyethyl acrylate.
[0050] The preparation method of the organic molybdenum compound is as follows:
[0051] (1) 0.1 mol of 1-bromotetradecane, 0.12 mol of N-methyldiethanolamine and 100 mL of acetonitrile reagent were added to a round-bottom flask in sequence, the temperature was slowly raised to 85° C., and the mixture was stirred at 200 rpm for 24 h. The acetonitrile solvent was removed in a vacuum evaporator, and 100 mL of ethyl acetate was added. A white solid was obtained after filtration, and the solid was washed with a small amount of ethyl acetate for 5 times and dried in a vacuum at 75° C. for 48 h to obtain intermediate A;
[0052] (2) Dissolve 0.12 mol of molybdenum acetylacetonate powder in hot ethanol, slowly add 0.13 mol of alcohol solution of intermediate A (add 30 mL of ethanol) while stirring, stir evenly, heat to 85° C., reflux for 24 h, and remove the solvent by vacuum distillation to obtain a dark blue powder, namely intermediate B;
[0053] (3) 0.10 mol of intermediate B and 0.11 mol of oleic acid were dissolved in 70 mL of dichloromethane solution, and then 40 mL of 2 mol / L sodium hydroxide aqueous solution was added dropwise to the mixed solution. The mixture was stirred for 12 h, and the color of the product solution changed from dark blue to green. 30 mL of dichloromethane was taken to extract the product, and then the product was washed with distilled water until no precipitation was generated in the silver nitrate solution. The product was dried to obtain an organic molybdenum compound.
[0054] The preparation method of coumarin derivatives is as follows:
[0055] Add 2.62 g of glycine methyl ester hydrochloride and 20 mL of deionized water to a round-bottom flask, adjust the pH to 8.5-9.0 with triethylamine, add 5.51 g of salicylaldehyde to the reaction system, and react at room temperature for 24 h. During the reaction, an orange suspended substance appears in the bottle. Filter and wash to obtain an orange solid crude product, place it in a vacuum drying oven to dry, and use a DMF-H2O system for recrystallization to obtain 3-(2-(hydroxybenzylidene)amino)
[0056] Coumarin;
[0057] The prepared 3-(2-(hydroxybenzylidene)amino)coumarin was transferred into a 250mL three-necked flask, and 100mL of dilute hydrochloric acid (concentrated hydrochloric acid and water were mixed in a volume ratio of 1:2) was added to the flask for hydrolysis at room temperature for 60min, and the pH was adjusted to 8-9. A large amount of brown suspended matter was precipitated in the flask. After the flask was cooled, it was filtered and washed to obtain a reddish-brown solid, which was recrystallized using EtOH:H2O in a volume ratio of 1:3. Then 4g of acryloyl chloride and 20mL of toluene were added to the system, the pH was adjusted to 7.5, and the reaction was carried out at 50°C for 2h and dried to obtain a coumarin derivative.
[0058] Embodiment 3
[0059] The method for preparing a flame-retardant and light-resistant core-shell water-based acrylic resin coating is characterized in that the coating is prepared according to the following steps:
[0060] (1) Preparing a core layer emulsion: adding 40 g of water, 1.5 g of an emulsifier prepared by mixing sodium dodecylbenzene sulfonate and AEO-9 in a mass ratio of 2:1, and 3.4 g of methacrylic acid to a reaction container, mixing and stirring evenly, heating to 45° C., stirring and reacting for 60 min, adding monomer A and 0.01 mol of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO), and 1.6 g of an organic molybdenum compound, and emulsifying for 25 min; heating to 65° C. and starting to reflux water, heating to 85° C., and dripping 5.55 g of a potassium persulfate solution dissolved in 5 g of water, and continuing the dripping time for 1.2 h, and reacting at 80° C. for 1.5 h to obtain a core layer emulsion;
[0061] (2) adding all the monomers B and 5.3 g of potassium persulfate dissolved in 5 g of water to the core layer emulsion obtained in step (1) at the same time, the dropping time lasts for 1 hour, the reaction is stirred at 80° C. for 1.5 hours, 1.8 g of hydroxypropyl propargyl ether, 1.65 g of coumarin derivative and 0.02 g of glutaric acid are added, the reaction is carried out at 65° C. for 1 hour, the temperature is lowered to 50° C., 0.3 g of AEO-9, 0.1 g of zirconium sulfate, 0.15 g of aluminum sulfate and 0.05 g of sodium maleate are added, the reaction time is 30 minutes, and ammonia water is added to adjust the pH value to 7-8 to obtain the flame-retardant and light-resistant core-shell water-based acrylic resin coating;
[0062] The monomer A is prepared by mixing 3.5 g of ethyl acrylate, 4.5 g of methyl methacrylate and 3.5 g of hydroxyethyl acrylate;
[0063] The monomer B is prepared by mixing 4 g of ethyl acrylate, 6 g of methyl methacrylate and 4.5 g of hydroxyethyl acrylate.
[0064] The preparation method of the organic molybdenum compound is:
[0065] (1) 0.1 mol of 1-bromotetradecane, 0.11 mol of N-methyldiethanolamine and 100 mL of acetonitrile reagent were added to a round-bottom flask in sequence, the temperature was slowly raised to 75° C., and the mixture was stirred at 200 rpm for 20 h. The acetonitrile solvent was removed in a vacuum evaporator, and 90 mL of ethyl acetate was added. A white solid was obtained after filtration and washed four times with a small amount of ethyl acetate, and dried in a vacuum at 65° C. for 40 h to obtain intermediate A;
[0066] (2) Dissolve 0.11 mol of molybdenum acetylacetonate powder in hot ethanol and slowly add
[0067] 0.115 mol of intermediate A in ethanol (30 mL of ethanol) was stirred evenly, heated to 75°C, refluxed for 20 h, and the ethyl acetate solvent was removed by vacuum distillation to obtain a dark blue powder, namely intermediate B;
[0068] (3) 0.10 mol of intermediate B and 0.11 mol of oleic acid were dissolved in 65 mL of dichloromethane solution, and then 40 mL of 1.5 mol / L sodium hydroxide aqueous solution was added dropwise to the mixed solution. The mixture was stirred for 11 h, and the color of the product solution changed from dark blue to green. 30 mL of dichloromethane was taken to extract the product, and then the product was washed with distilled water until no precipitation was generated in the silver nitrate solution. The product was dried to obtain an organic molybdenum compound.
[0069] The preparation method of coumarin derivatives is as follows:
[0070] Add 2.62 g of glycine methyl ester hydrochloride and 18 mL of deionized water to a round-bottom flask, adjust the pH to 8.5-9.0 with triethylamine, add 5.51 g of salicylaldehyde to the reaction system, and react at room temperature for 18 h. During the reaction, an orange suspended substance appears in the bottle. Filter and wash to obtain an orange solid crude product, place it in a vacuum drying oven to dry, and use a DMF-H2O system for recrystallization to obtain 3-(2-(hydroxybenzylidene)amino)coumarin;
[0071] The prepared 3-(2-(hydroxybenzylidene)amino)coumarin was transferred into a 250mL three-necked flask, and 100mL of dilute hydrochloric acid (concentrated hydrochloric acid and water were mixed in a volume ratio of 1:2) was added to the flask for hydrolysis at room temperature for 45min, and the pH was adjusted to 8-9. A large amount of brown suspended matter was precipitated in the flask. After the flask was cooled, it was filtered and washed to obtain a reddish-brown solid, which was recrystallized using EtOH:H2O in a volume ratio of 1:3. Then 3.5g of acryloyl chloride and 15mL of toluene were added to the system, the pH was adjusted to 7.5, and the reaction was carried out at 45°C for 1.5h and dried to obtain a coumarin derivative.
[0072] The prepared acrylic resin coating was poured into a polytetrafluoroethylene mold with a thickness of 3 mm, and the droplet test, cone calorimetry, light resistance and other tests were carried out.
[0073] The following is a molten drop test:
[0074] (1) Sample preparation: The prepared acrylic resin film was placed in a constant temperature and humidity chamber set at 23°C ± 0.5°C and 50% ± 5% humidity for 48 h, and then taken out and cut into samples of 110 cm × 10 cm × 3 mm. Two sets of samples were prepared, with 5 samples in each set.
[0075] (2) Parameter setting: Clamp about 5 mm from the top so that the sample is vertically downward. Place a rosin board at the bottom of the sample, and pad about 0.3 g of absorbent cotton on the board, evenly place it on the board. Adjust the gas flow rate to 105±5 mL / min so that the flame height reaches 20±1 mm. Set the combustion time to 10 s.
[0076] (3) Flame recording: After setting the parameters, start the flame ignition. After the 10s ignition, press the afterflame time start button. When the sample combustion is finished and only sparks are left, press the afterflame combustion end button to enter the afterburning time. When the sample is completely extinguished, press the afterburning time end button and record the afterflame time and afterburning time.
[0077] (4) Molten droplet observation: During the combustion process, pay attention to whether the combustion produces molten droplets, and whether the molten droplets dripping onto the absorbent cotton below will cause secondary combustion, and record the observation results.
[0078] Lightfastness is tested by keeping the distance between the sample and the light source at 25cm under a 300W ultraviolet lamp for 48 hours, observing the color change, and testing it on a HZ-3017 bulb-type yellowing resistance instrument. The lightfastness level is determined by comparing it with a colorimetric card.
[0079] Use JZ-300 universal colorimeter, and put the modified sample and blank into the bulb-type light source yellowing resistance test box at the same time. Keep the distance between the sample and the light source at 25cm under a 300W ultraviolet lamp, keep the temperature in the box at 60℃, and illuminate for 48 hours. Record the various values of the colorimeter to obtain the color difference value ΔE to describe the light resistance of acrylic resin. ΔE represents the degree of color change. The larger the ΔE, the more obvious the color change. Generally speaking, a ΔE value of 0 to 1.5 is a slight change; a ΔE value of 1.5 to 3 is a perceptible change; and a ΔE value of 3.0 to 6.0 is a significant change (see Wang Fang, Dang Gaochao, Wang Liqin, Photodegradation of Several Organic Cultural Relics Protection Polymer Coatings [J]. Journal of Northwest University, 2005, 35(5): 56-58.)
[0080] Reflectivity determination method: Use a Gretag Macbeth Coloreye spectrophotometer (D65 light source, 10 degree observer, including UV) to measure the emission level of the resin from 360nm to 750nm, wherein the reflectivity at 660nm is defined as the maximum emissivity in this technical solution.
[0081] The ASTM E1354-1990 (2004 standard) was used to analyze and measure the sample using the Cone Calorimeter 2000 of the British FTT Company. The sample was 10cm×10cm, 3mm thick, and the thermal radiation power was 12kW / m 2 , determine the maximum heat release rate pkHHR kW / m 2 ,THR total heat release MJ / m2,pSPR smoke generation rate reaches peak value m 2 / s and maximum total smoke release (TSR) m 2 / m 2 The fire performance index (FRI) is the ratio of the time to ignition (TTI) to the peak heat release rate (pHRR). 2 kW -1 ) is the standard for measuring the flashover time at a fire scene. The larger the FRI value, the longer the flashover time and the longer the time it takes for people at the fire scene to escape.
[0082] Table 1 Properties of flame-retardant and light-resistant water-based core-shell acrylic resin films
[0083]
[0084] The comparative example adopts Example 3 of CN112322132A. From the flame retardancy (pkHHR, THR, pSPR smoke generation rate, TSR, FRI and droplet situation) and light resistance index (light resistance ΔE, light resistance grade and emissivity) of the film formed by the flame retardant and light-resistant water-based core-shell acrylic resin in Table 1, it can be found that the light resistance changes slightly. The light resistance and flame retardancy of the present invention are better than those of the comparative example, indicating that the present invention significantly improves the light resistance of the core-shell acrylic resin.
[0085] Table 2 Performance of the film formed by flame retardant and light resistant water-based core-shell acrylic resin (flame retardant changes without adding some materials) Taking Example 3 as an example
[0086]
[0087] As can be seen from Table 2, the THR, pSPR smoke generation rate, TSR and droplet index of the polymer obtained without adding organic molybdenum compounds, oleic acid, acetylacetonate molybdenum powder and DOPO are all improved, showing the influence of the above substances on the flame retardancy of acrylic resin.
[0088] Table 3 Effect of light resistance of unadded materials (taking Example 3 as an example)
[0089]
[0090] As can be seen from Table 3, the light resistance and glutaric acid indices decreased without the addition of coumarin derivatives, salicylaldehyde, hydroxypropyl propargyl ether, and aluminum sulfate, indicating the necessity of the above substances for light resistance.
[0091] The following is to examine the light resistance:
[0092] Lightfastness is determined by keeping the distance between the sample and the light source at 25 cm under a 300W ultraviolet lamp for 120 hours, observing the color change, and comparing with the color chart to determine the lightfastness level;
[0093] Use JZ-300 universal colorimeter, and put the modified sample and blank into the bulb-type light source yellowing resistance test box at the same time. Keep the distance between the sample and the light source at 25 cm under a 300W ultraviolet lamp, keep the temperature in the box at 60°C, and illuminate for 120 hours.
[0094] Table 4 Lightfastness and Durability
[0095]
[0096] It can be found from Table 4 that the light resistance level under ultraviolet light irradiation is still high, and the emissivity is also high, while the light resistance without adding aluminum sulfate and zirconium sulfate decreases significantly, indicating that aluminum sulfate and zirconium sulfate play an obvious role in it, and the reaction is stable after adding glutaric acid and sodium maleate, which can promote the improvement of light resistance.
[0097] The acrylic resin film obtained by adding coumarin derivatives and hydroxypropyl propargyl ether does not turn yellow when exposed to light for 48 hours at a temperature of 60°C, while the acrylic resin film obtained without adding coumarin derivatives and hydroxypropyl propargyl ether appears light yellow.
Claims
1. Key materials required for the preparation of flame-retardant and light-resistant core-shell water-based acrylic resin coatings, characterized in that: The flame retardancy and light resistance of its water-based acrylic resin coatings are mainly achieved by organic molybdenum compounds and coumarin derivatives; The preparation method of the organic molybdenum compound is as follows: (1) 0.1 mol of 1-bromotetradecane, 0.11-0.12 mol of N-methyldiethanolamine and 100 mL of acetonitrile were added to a round-bottom flask in sequence, the temperature was slowly raised to 70-85° C., and the mixture was stirred at 200 rpm for 16-24 h. The acetonitrile solvent was removed by a vacuum evaporator, and 80-100 mL of ethyl acetate was added. A white solid was obtained after filtration, and the solid was washed with a small amount of ethyl acetate for 4-5 times, and vacuum dried at 60-75° C. for 32-48 h to obtain intermediate A; (2) dissolving 0.11-0.12 mol of molybdenum acetylacetonate powder in hot ethanol, slowly adding 0.10-0.13 mol of ethanol solution of intermediate A while stirring, stirring evenly, heating to 70-85° C., reflux for 16-24 h, and removing the solvent by reduced pressure distillation to obtain a dark blue powder, namely intermediate B; (3) 0.10 mol of intermediate B and 0.11 mol of oleic acid were dissolved in 60-70 mL of dichloromethane solution, and then 40 mL of 1-2 mol / L sodium hydroxide aqueous solution was added dropwise to the mixed solution, and the reaction was stirred for 10-12 hours. The color of the product solution changed from dark blue to green. 30 mL of dichloromethane was taken to extract the product, and then the product was washed with distilled water until no precipitation was generated in the silver nitrate solution, and the product was dried to obtain an organic molybdenum compound; The preparation method of coumarin derivatives is as follows: Add 2.62 g of glycine methyl ester hydrochloride and 15-20 mL of deionized water to a round-bottom flask, adjust the pH to 8.5-9.0 with triethylamine, then add 5.51 g of salicylaldehyde to the reaction system, and react at room temperature for 12-24 h. During the reaction, an orange suspended substance appears in the bottle, which is filtered and washed to obtain an orange solid crude product, which is placed in a vacuum drying oven for drying and recrystallized using a DMF-H2O system to obtain 3-(2-(hydroxybenzylidene)amino)coumarin; The prepared 3-(2-(hydroxybenzylidene)amino)coumarin was transferred into a 250mL three-necked flask, and 100mL of dilute hydrochloric acid, which was a mixture of concentrated hydrochloric acid and water in a weight ratio of 1:2, was added to the flask, and hydrolysis was carried out at room temperature for 30-60min, and the pH was adjusted to 8-9. A large amount of brown suspended matter was precipitated in the flask. After the flask was cooled, it was filtered and washed to obtain a reddish-brown solid, which was recrystallized using EtOH:H2O in a volume ratio of 1:3, and dried. Then 3-4g of acryloyl chloride and 10-20mL of toluene were added to the system, the pH was adjusted to 7.5, and the reaction was carried out at 40-50°C for 1-2h, and dried to obtain a coumarin derivative.
2. The key materials required for preparing the flame-retardant and light-resistant core-shell water-based acrylic resin coating according to claim 1, and the method for preparing the flame-retardant and light-resistant core-shell water-based acrylic resin coating is: Prepare according to the following steps: (1) Preparing a core layer emulsion: adding 30-50 g of water, 1.2-1.9 g of emulsifier A, and 2.6-4.2 g of methacrylic acid to a reaction container, mixing and stirring evenly, heating to 40-45° C., stirring and reacting for 60 min, adding monomer A and 0.01 mol of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and 1.1-2.2 g of an organic molybdenum compound, emulsifying for 20-30 min; heating to 65° C., passing reflux water, heating to 80-90° C., dropping 0.4-0.7 g of initiator, dropping for 1-1.5 h, reacting at 70-90° C. for 1-2 h, and obtaining a core layer emulsion; (2) To the entire core layer emulsion obtained in step (1), all monomers B and 0.2-0.4 g of initiator are simultaneously added dropwise for 1 h, and the mixture is stirred at 75-85° C. for 1.5 h. 1.0-2.6 g of hydroxypropyl propargyl ether, 0.7-2.6 g of coumarin derivative and 0.02 g of glutaric acid are added, and the mixture is reacted at 60-70° C. for 1 h. The mixture is cooled to 50° C., and 0.3 g of emulsifier B, 0.1 g of zirconium sulfate, 0.1-0.2 g of aluminum sulfate and 0.05 g of sodium maleate are added, and the reaction time is 30 min. Ammonia water is then added to adjust the pH value to 7-8, and the flame-retardant and light-resistant core-shell water-based acrylic resin coating is obtained. The monomer A is prepared by mixing 3-4g of ethyl acrylate, 4-5g of methyl methacrylate and 3-4g of hydroxyethyl acrylate; The monomer B is prepared by mixing 2-6 g of ethyl acrylate, 4-8 g of methyl methacrylate and 3-6 g of hydroxyethyl acrylate.
3. The key material required for the preparation of the flame-retardant, light-resistant core-shell water-based acrylic resin coating according to claim 2, characterized in that: The initiator is any one of ammonium persulfate, potassium persulfate and potassium hydrogen persulfate.
4. The key material required for the preparation of the flame-retardant, light-resistant core-shell water-based acrylic resin coating according to claim 2, characterized in that: The emulsifier A is prepared by mixing sodium dodecylbenzene sulfonate and AEO-9 in a weight ratio of 2:
1.
5. The key material required for the preparation of the flame-retardant, light-resistant core-shell water-based acrylic resin coating according to claim 2, characterized in that: The emulsifier B is AEO-9.
Citation Information
Patent Citations
Preparation method of carbon nanotube and graphene-modified light-resistant waterborne acrylate resin coating
CN108624183A
Preparation method of flame-retardant core-shell environment-friendly waterborne acrylate resin coating
CN110204989A
Preparation method of flame-retardant core-shell type environment-friendly water-based resin coating
CN112322132A
Preparation method of flame-retardant water-based core-shell acrylate resin coating
CN112409877A